SECOND LANGUAGE ACQUISITION IN TEACHING ENGLISH AS A SECOND LANGUAGE - Shopia Azhar (Universitas Islam Negeri Alauddin Makassar, 2015)
This article tries to answer some of the following questions : Why is it that some individuals are more successful than others in mastery of a second language? Why does one person seem to learn faster than another even if both are in the same situation? Or why does a person become more proficient in some parts of the language system (i.e., oral production and aural comprehension) than in other parts (i.e., written production and reading comprehension)? These are questions that linguists and language teachers have been asking for years. Recently several models of the second language acquisition process have been developed in an attempt to explain the interaction of variables which affect second language acquisition and the cognitive strategies that determine the form and course of acquisition. Because second language (L2) acquisition is a very complex process, no one model yet captures all of its facets. The purpose of this paper is to survey some of the current research and to review several models of L2 acquisition. The emphasis will be on the role of the learner rather than that of the teacher.